DFT Study on the Mechanism of Water Oxidation Catalyzed by a Mononuclear Copper Complex (Communications in Computational Chemistry, 2025)
This work employed DFT calculations to elucidate the mechanism of water oxidation reaction catalyzed by a mononuclear pyridine-based copper complex, which was reported to be a homogeneous water oxidation catalyst in a pH=11.84 buffersolution. The coordination of one water molecule with the ${\rm Cu}^{{\rm II}}$ center leads to the generation of the ${\rm Cu}^{{\rm II}}-{\rm OH}_2 (1-{\rm H}_2{\rm O}).$ The activespecies $({\rm Cu}^{{\rm IV}}={\rm O, 3})$ is generated after two subsequent proton-coupled electron transfer processes from $1-{\rm H}_2{\rm O}.$ $3$ triggers the O-O bond formation via water nucleophilic attack mechanism. The triplet ${\rm O}_2$ can be released after following two oxidation processes.The formation of the O-O bond is the rate-determining step for the catalytic cycle associated with a total barrier of 19.3 kcal/mol.